Procedimentos destinados ao aumento de vocalizações em indivíduos com Transtorno do Espetro Autista (TEA) e outros transtornos do neurodesenvolvimento: uma revisão da literatura - Oddone, Alessandra Laranjeira (2022)
The present study aimed to carry out a literature review of articles on behavior analysis, in national and foreign journals, aimed at the acquisition and expansion of vocal repertoire in children with neurodevelopmental delays, thus verifying relevant variables for the effectiveness of the procedures. The articles were collected in three databases: PsycINFO, PubMed and Scientific Electronic Library Online (Scielo), using the keywords: echoic training, mand training, intraverbal training, echoic to mand training, vocal imitation, stimulus-pairing, language development, language delay, autism and vocalization. Experimental research based on the theoretical framework of behavior analysis was selected. We found 31 studies in which 171 participants participated. Studies with children under five years old predominated (77.7%), with Autism Spectrum Disorder (ASD) being the most reported diagnosis (38.5% of participants). The target behaviors of the interventions were: vocalizations (24), echoic (5), tact (2) and mand (2). Most of the research aimed at increasing or establishing vocalizations applied the Stimulus-Stimulus Pairing (SSP) procedure. It was possible to calculate the effect size by means of the Nonverlap off All Paires (NAP) calculation in 19 articles. Procedures with strong effects were SSP for teaching vocalizations, delaying the echoic model for teaching mand and echoic behavior, echoic training and differential reinforcement for teaching tact. New studies are suggested to expand the possibilities of analyzing the effectiveness of the procedures used